Altersbezogene Vorsorgeintentionen und deren Ausrichtung bei nicht obligatorisch versicherten Gründern – Pilotstudie - Zapfel, Stefan; Stumpf, Felix (2014)

Die berufliche Strukturierung der frühen Erwerbsphase: Ereignisanalysen zur Beschäftigungsstabilität - Stumpf, Felix; Damelang, Andreas; Schulz, Florian (2012)

Foreign credential recognition and immigrants’ chances of being hired for skilled jobs – Evidence from a survey experiment among employers - Damelang, Andreas; Ebensperger, Sabine; Stumpf, Felix (Social Forces, 2020)

"Freiwillig pflichtversichern“? Alternativen der Alterssicherung von nicht obligatorisch versicherten Selbständigen. - Zapfel, Stefan; Stumpf, Felix (2014)

Haben die Freien Berufe Konjunktur? Konjunkturtrends auf Basis vergleichbarer Frühindikatoren für Freie Berufe und gewerbliche Wirtschaft - Stumpf, Felix; Kurz, Birgit (Daten in der wirtschaftswissenschaftlichen Forschung, 2013)

How National Institutions Shape Skilled Immigrants’ Chances of Getting Hired: Evidence from Harmonised Factorial Surveys with Employers in Germany and England - Stumpf, Felix; Damelang, Andreas; Abraham, Martin; Ebensperger, Sabine (Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2020)

How National Institutions Shape Skilled Immigrants’ Chances of Getting Hired: Evidence from Harmonised Factorial Surveys with Employers in Germany and England - Stumpf, Felix; Damelang, Andreas; Abraham, Martin; Ebensperger, Sabine (Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2020)
This study provides novel insights into the institutional conditions under which skilled immigrants get hired for skilled jobs in different countries. We argue that immigrants’ hiring chances depend on the interplay between institutions in sending countries, which determine the type of education that immigrants bring, and institutions in receiving countries, which shape employers’ preferences for certain types of education. We develop a research design that considers this interplay and allows us to directly compare how education from sending countries with different institutional arrangements is rated by employers in two countries with widely divergent institutional contexts of reception, Germany and England. Using harmonised factorial surveys, we simulate hiring processes and evaluate the chances of German and English employers inviting foreign-educated immigrants to interviews for jobs commensurate with their education. The survey design makes it possible to experimentally vary the institutional settings in which immigrants acquired their education in the sending country, and isolate their effect on employers’ ratings. Our key finding is that immigrants from sending countries with highly standardised occupation-orientated education systems prevail in the hiring competition, irrespective of the education system in the receiving country.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Educational systems; Foreign education; Labour market; Vignette study; Vocational education and training

Immigrants’ Labour Market Disadvantages Across Western Europe: the Role of Composition and Context - Damelang, Andreas; Ebensperger, Sabine; Stumpf, Felix (Journal of International Migration and Integration, 2021)

Leseförderung durch Teilhabe: Die Jugendjury zum Deutschen Jugendliteraturpreis - Brendel-Perpina, Ina; Stumpf, Felix (2013)

Moderne Berufsstrukturen in der Elektroindustrie: Der zweijährige Ausbildungsberuf Industrieelektriker/-in - Krenn, Sylvia; Stumpf, Felix (2012)

The Hiring Prospects of Foreign-Educated Immigrants: A Factorial Survey among German Employers - Damelang, Andreas; Abraham, Martin; Ebensperger, Sabine; Stumpf, Felix (Work Employment and Society, 2019)

Untersuchung des Bedarfs an einem Berufsprofil „Fügetechnische Fachkraft“ - Zeller, Beate; Küfner, Christine; Neumann, Florian; Krenn, Sylvia; Stumpf, Felix (2011)

Verkehrserziehung in Kindergärten und Grundschulen - Funk, Walter; Hecht, Phillip; Nebel, Sophia; Stumpf, Felix (2013)